Molecular Mechanism of Action of Plant DRM De Novo DNA Methyltransferases - Zhong, Xuehua; Du, Jiamu; Hale, Christopher J.; Gallego-Bartolome, Javier; Feng, Suhua; Vashisht, Ajay A.; Chory, Joanne; Wohlschlegel, James A.; Patel, Dinshaw J.; Jacobsen, Steven E. (Cell, 2014)
DNA methylation is a conserved epigenetic gene-regulation mechanism. DOMAINS REARRANGED METHYLTRANSFERASE (DRM) is a key de novo methyltransferase in plants, but how DRM acts mechanistically is poorly understood. Here, we report the crystal structure of the methyltransferase domain of tobacco DRM (NtDRM) and reveal a molecular basis for its rearranged structure. NtDRM forms a functional homodimer critical for catalytic activity. We also show that Arabidopsis DRM2 exists in complex with the small interfering RNA (siRNA) effector ARGONAUTE4 (AGO4) and preferentially methylates one DNA strand, likely the strand acting as the template for RNA polymerase V-mediated noncoding RNA transcripts. This strand-biased DNA methylation is also positively correlated with strand-biased siRNA accumulation. These data suggest a model in which DRM2 is guided to target loci by AGO4-siRNA and involves base-pairing of associated siRNAs with nascent RNA transcripts. [Display omitted] •Structural and molecular basis for rearranged mechanism of de novo methyltransferase•Tobacco DRM forms a functional homodimer critical for catalytic activity•Arabidopsis DRM2 interacts with AGO4 and preferentially methylates one DNA strand•AGO4-siRNA guides DRM2 to methylate a template DNA strand for Pol V transcription The structure of tobacco DRM reveals that, although its methyltransferase domain is rearranged, it retains a classic class I methyltransferase fold. DRM interacts with AGO4 and preferentially methylates one DNA strand, suggesting a strand-specific DNA methylation mechanism.